ANALISIS KEEFEKTIFAN BELAJAR MATEMATIKA MELALUI PENDEKATAN STOP THINK DO PADA SISWA MTs. BUDI AGUNG T.P 2013/2014 - Chairi Mutia Lubis; Edy Surya (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The study was conducted to determine the effectiveness of learning mathematics through stop approach do the students think MTs . Budi Agung Medan T.P 2013/2014 . This research is quantitative . The instrument uses observation and tests . The population in this study all students in grade VIII . RESULTS: The percentage of students overall effectiveness by 75 % , entrance to the effective criteria . For more information the t test analysis and test table = 1.99 thitung gain for the index since thitung 6.696 > t table Ha is accepted then there are differences in the average index gain experimental class and the control class known experimental class learning outcomes better than the control class , so that learning mathematics through stop think do an effective approach .